Identification of putative orthologous genes for the phylogenetic reconstruction of temperate woody bamboos (Poaceae: Bambusoideae). (2nd April 2014) - Zhang, Li‐Na; Zhang, Xian‐Zhi; Zhang, Yu‐Xiao; Zeng, Chun‐Xia; Ma, Peng‐Fei; Zhao, Lei; Guo, Zhen‐Hua; Li, De‐Zhu
Abstract The temperate woody bamboos (Arundinarieae) are highly diverse in morphology but lack a substantial amount of genetic variation. The taxonomy of this lineage is intractable, and the relationships within the tribe have not been well resolved. Recent studies indicated that this tribe could have a complex evolutionary history. Although phylogenetic studies of the tribe have been carried out, most of these phylogenetic reconstructions were based on plastid data, which provide lower phylogenetic resolution compared with nuclear data. In this study, we intended to identify a set of desirable nuclear genes for resolving the phylogeny of the temperate woody bamboos. Using two different methodologies, we identified 209 and 916 genes, respectively, as putative single copy orthologous genes. A total of 112 genes was successfully amplified and sequenced by next‐generation sequencing technologies in five species sampled from the tribe. As most of the genes exhibited intra‐individual allele heterozygotes, we investigated phylogenetic utility by reconstructing the phylogeny based on individual genes. Discordance among gene trees was observed and, to resolve the conflict, we performed a range of analyses using BUCKy and HybTree. While caution should be taken when inferring a phylogeny from multiple conflicting genes, our analysis indicated that 74 of the 112 investigated genes are potential markers for resolving the phylogeny of the temperate woody bamboos.